Syria's leadership challenges: the trials ahead - Aldalala'a, Nath (2025)
The rapid collapse of the al-Assad regime in the face of opposition forces led by Hay’yat Tahrir al-Sham (HTS) came as a shock to the rest of the world. However, if it assumes governance, HTS faces an intricate and factionalised domestic landscape compounded by competing regional interests in the Syrian conflict. HTS’ Islamist roots, along with its past ties to al-Qaeda, present significant obstacles to its ability to secure Arab and international legitimacy and sustainable long-term support.